Health Related Quality of Life Among Coronary Artery Bypass Graft Patient Attended at Combined Military Hospital, Dhaka - Irfan, SM Nurul; Rahaman, Md. Mahbubur; Noman, Abu; Mithun, Sangita (Anwer Khan Modern Medical College Journal, 2013)
This descriptive type of cross sectional study was carried out among purposively selected 90 coronary artery bypass graft operated patients attended at cardiovascular surgery out patient department of combined military hospital, Dhaka from 01 March 2012 to 30 June 2012 with the objective to assess the quality of life by using the RAND Medical Outcomes Short Form 36 (SF- 36) questionnaire. The population studied had a mean age of 54.60 years with 92.2% were male and 7.8% were female. Most of the respondents were retired (43.3%) followed by service personnel (38.9%). Regarding educational qualification, most of them were between class VIII to SSC and 95.6% were Muslim. The mean monthly income of the respondents was Tk. 18127.78. The findings showed that post CABG respondents possessed a good level of QOL with an average score of 86.0921. The mental components score (87.8571) was found to be higher than physical component score (84.9153). It was found that the association between age and physical functioning domain of physical component was statistically significant (r= -.189*, p<0.05) and association between all other domains (role physical, bodily pain, general health, vitality, social functioning, role emotional and mental health) were statistically not significant. The study also revealed a negative correlation of total quality of life with age but positive correlation with other socio demographic characteristics (level of income, education and occupation) though all of the relations were statistically not significant. No statistically significant difference revealed with the different domains of quality of life and socio demographic characteristics. In regards to the monthly income, highest score noted in Tk. 10000-30000 income groups in all the domains. Respondents' occupation showed significant difference with the general health domain (F= 3.456, p <0.05) and physical component summary (F= 2.969, p <0.05) of the SF- 36 items. The education level showed significant difference with the physical functioning of physical component domain (F= 2.675, p <0.05). The findings showed that the highest score was for HSC education in both the components of quality of life. The post CABG respondents possessed a good level of QOL with good mental components score than physical component score. It is also revealed from the study that with increasing age the physical functioning of the patient decreases. From the study it depicts that higher education, better occupation and good monthly income of the respondents have better quality of life out come than that of others. Study on larger sample size may be carried out for more accurate results on quality of life after CABG operation. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 10-17 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16918